Fenofibrate-Induced Lichenoid Drug Eruption: A Rare Culprit - Fayeza Mohammed (Case Reports in Dermatology, 2017)
A lichenoid drug eruption is a rare side effect which can occur following the administration of several different medications. Here we describe a unique case of fenofibrate as the causative agent of a lichenoid drug eruption. This case highlights a rare and clinically significant dermatologic side effect of fenofibrate. In addition, we report a potential familial association which underscores the potential for underlying genetic mechanisms to be contributory to lichenoid drug eruptions. A reminder of the physical characteristics of lichen planus, knowledge of the temporal relation between administration of medications and a lichenoid drug eruption, recognition of the effect of UV exposure on lichenoid drug eruptions, and realization for the potential of symptoms to persist despite discontinuation of an offending agent can aid practitioners in promptly diagnosing lichenoid drug eruptions and initiating appropriate therapy.